2020
DOI: 10.21203/rs.3.rs-56553/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on acute stroke reperfusion therapy: data from the Lyon Stroke Center Network

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic would have particularly affected acute stroke care. However, its impact is clearly inherent to the local stroke network conditions. We aimed to assess the impact of COVID-19 pandemic on acute stroke care in the Lyon comprehensive stroke center during this period.MethodsWe conducted a prospective data collection of patients with acute ischemic stroke (AIS) treated with intravenous thrombolysis (IVT) and/or mechanical thrombectomy (MT) during the COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As data on IVT were not available exhaustively, they were not analysed in our study. This should be addressed in future studies to explore the lower rates of IVT reported in local stroke centres in France [31] and abroad [6,28], and the delay in administering endovascular treatments [4,6,28,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As data on IVT were not available exhaustively, they were not analysed in our study. This should be addressed in future studies to explore the lower rates of IVT reported in local stroke centres in France [31] and abroad [6,28], and the delay in administering endovascular treatments [4,6,28,33].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, this could be attributable to the higher severity of stroke patients hospitalized during the lockdown, mainly characterized by large vessel occlusion. Of note, in another French study based in a single centre in Lyon, rates of MT remained unchanged during the COVID‐19 outbreak [31], whereas lower rates of all revascularization treatments were observed in Alsace, one of the centres of the epidemic in France [32]. Local experiences might differ from national observations, as the different French territories were not equally affected by the COVID‐19 spread.…”
Section: Discussionmentioning
confidence: 99%